Assessment of Flood Vulnerability in Egor Local Government Area, Edo State Using Analytical Hierarchical Process (AHP) Model - Nwodo, G. O.; Eze, Ikechukwu Roland (NIU Journal of Social Sciences, 2026)
Floods are entirely natural disasters caused by a variety of fundamental factors, the most common of which are climatological in character. However, human misuse or exploitation of the environment is also a major contributing factor. Floods are regarded as the world's worst natural disaster which motivates this research. This research aims to investigate the flood vulnerability in Egor local government area of Edo state by integrating the Analytical Hierarchy Process (AHP) and remote sensing/GIS to derive a flood vulnerability map of Egor local government area. In this research seven parameters elevation, slope, drainage density, soil type, distance from streams, rainfall and land use and land cover were considered and their weight of importance were determined from pairwise comparison using the responses of professionals in the area of flood modelling and geoinformatics. Multiple sources of secondary data like 30M resolution Landsat 9 (Band 8 Panchromatic 0.503 – 0.676) satellite data derived from United States Geological Services (USGS), Tropical Rainfall Measuring Mission (TRMM) as well as other primary data gotten from response of questionnaire administered. The resulting map was classified into five levels of flood vulnerability and the communities were characterized according to their level of vulnerability. Findings showed that the villages Ogunwenyi, Obanyotor, Ogboyoko, Useh and Oghoghugbo were all classified under highly vulnerable to flooding. Although, Ugbowo and Oghoghugbo are not threatened at the moment but projection shows that they may become threatened if the conditions contributing to flooding are not appropriately managed.  This research offers an approach that is very useful in flood management and mitigation. It also creates avenue for land planners and policy makers to know the areas that are projected to suffer from flooding and those that are less threatened which preventive measures can be developed against these challenges. The vulnerability model produced in this work should serve as a guide to policy makers, and planners for appropriate managements of flood events and initiation of enlightenment programs to citizens on sustainable ecological land conservation. Keywords: Flood vulnerability mapping, Analytic Hierarchy Process (AHP), Remote sensing and GIS, Land use/land cover, Landsat 9